(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Against the backdrop of newborn genetic screening and pandemics, this article examines disputes between parents, acting as proxies for their children, and healthcare professionals. While some will support parents, others will push-back against proxy consent and the right to veto actions that are proposed by the professionals. Whereas in ordinary times, such a push-back might seek to displace or downgrade parental rights (e.g. by appealing to professional duty or the optimisation of health) or to de-centre or dilute consent, in extraordinary times, rights and consent are superseded by appeals to responsibility, solidarity, and even "states of exception".